Buying History Of Organic Food By Consumers In An Emerging Market - Sudarnice Sudarnice; Zainul Wasik; Dominicus Wahyu Pradana (Journal of Managerial Sciences and Studies, 2024)
Consumption of organic food is rising quickly in emerging nations. Organic food is a specific sort of food product with rigorous cultivation methods. In actuality, only a small portion of consumers in many emerging economies are aware of this kind of cuisine. This study examines and evaluates the variables influencing consumers' attitudes about organic food and their intention to buy it in a developing market. The results of the study show that attitudes toward organic food are positively impacted by knowledge of organic food, information about organic food, concerns about food safety, and the perceived value of organic food. The findings also demonstrate that attitudes regarding organic food and perceived value have a major impact on purchasing intention.